Dinamika Komunikasi Santri Senior dan Junior Berkebutuhan Khusus di Pondok Pesantren - Aisyah, Dian Asmita; Kautsar, Kevin; Rangkuti, Achmad Harisman; Sari, Yunita (Jurnal Pustaka Komunikasi, 2025)
The phenomenon of seniority in Islamic boarding schools affects social dynamics so that there is a communication gap between senior and junior students which ends in bullying and persecution. The purpose of this study is to find out and analyze the interpersonal communication process between senior students and junior students at the Tahfiz Difabel K.H Ahmad Lutfi Fathullah Islamic Boarding School, South Jakarta. This research method is phenomenology. The theory used in this study is the Theory of Symbolic Interactionism. The results of the study show that the two dominant subjects use non-verbal communication, namely sign language and writing, although in the preparation of sentences there are often deviations in subjects, predicates, objects, and descriptions that are not in accordance with the rules of the Indonesian language. The communication barrier between the two subjects is the difference in skill levels in the use of sign language, so that often the recipient of the message does not understand the content of the message conveyed. Conflicts that occur between the two subjects, the resolution can be done quickly and efficiently.